THE IMPACT AND CORRELATION BETWEEN INFLATION, INTEREST RATES, AND ECONOMIC GROWTH IN INDONESIA. A FIVE-YEAR EXAMINATION (2019-2023) - Dewi, Dita Dismalasari; Alpiansah, Restu; Fitriani, Nurida; Baihaqi, Wikan Haqqu (Ekspansi: Jurnal Ekonomi, Keuangan, Perbankan, dan Akuntansi, 2024)
This study aims to investigate the influence of inflation and interest rates on Indonesia's economic growth. Employing a quantitative approach with the OLS regression technique, the study uncovers a significant relationship between inflation and economic growth. While high inflation can stimulate aggregate demand, boost investment, and drive economic expansion, it can also lead to economic uncertainty, erode household purchasing power, and hinder economic progress. Similarly, the study reveals a substantial impact of interest rates on economic growth. Low interest rates can encourage investment, enhance consumption, and propel economic growth. However, they can also trigger inflation, depreciate the exchange rate, and heighten the risk of financial crises.